Comorbidities in the idiopathic pulmonary fibrosis and progressive pulmonary fibrosis trial population: a systematic review and meta-analysis - Tyson M. Walters; Marcus C.H. Leong; Sydney B. Montesi; Christopher J. Ryerson; Yet H. Khor (European Respiratory Review)
Background Comorbidities can affect drug tolerability and health outcomes in patients with fibrotic interstitial lung disease. This systematic review and meta-analysis evaluated the types and prevalence of comorbidities amongst participants in pharmaceutical randomised controlled trials (RCTs) of idiopathic pulmonary fibrosis (IPF) and progressive pulmonary fibrosis (PPF). Methods Ovid Medline, Embase and CENTRAL databases were searched to identify phase II and III pharmaceutical RCTs of IPF or PPF. Reporting of comorbidities was evaluated, with meta-analyses being performed for the prevalence of different conditions. Results 34 articles were included, with 23 unique trials for IPF and one for PPF. A mean of 14 (range 1–44) comorbidities per study was reported in the IPF RCTs, with 11 being reported in the PPF RCT. Common comorbidities in the IPF RCT cohorts were systemic hypertension (pooled prevalence 45%, 95% CI 39–50%), hyperlipidaemia (38%, 95% CI 27–49%), gastro-oesophageal reflux disease (45%, 95% CI 36–54%), ischaemic heart disease (18%, 95% CI 13–42%) and diabetes mellitus (16%, 95% CI 13–20%). The PPF trial cohort had similar types and prevalence of comorbidities to those reported in the IPF trial cohorts. Conclusions Reporting of comorbidities varied across previous IPF RCTs, with limited data available for PPF. Prevalence of comorbidities reported in the IPF and PPF trial cohorts appear to be lower than those reported in prospective patient registries. There is a need for careful consideration of trial eligibility criteria with detailed reporting of comorbidities in future pharmaceutical RCTs to better understand the applicability of trial findings to real-world patients.